Liquefaction of corn stover using industrial biodiesel glycerol - Wang, Yuanhua; Wu, Jianping; Wan, Yiqin; Lei, Hanwu; Yu, Fei; Chen, Paul; Lin, Xiangyang; Liu, Yuhuan; Ruan, Roger (International Journal of Agricultural and Biological Engineering, 2009)
Corn stover was liquefied using an industrial biodiesel glycerol as a liquefying agent at atmospheric pressure and low temperature. It was found that the liquefaction yield increased with increasing glycerol-to-corn stover ratios. Sulfuric acid, added as a catalyst, was found to improve liquefaction yield. The hydroxyl number, moisture content, acid number, pH value, viscosity, density, elemental composition, and higher heating value of the liquefied corn stover samples were determined. The liquefied corn stover showed a high hydroxyl number of 270